Seasonal peaks and risk factors of respiratory syncytial virus infections related hospitalization of preterm infants in Taiwan. - Hsin Chi; Ching-Hu Chung; Yuh-Jyh Lin; Chyi-Her Lin (PLoS ONE, 2018)
OBJECTIVES:To assess the nationwide seasonal peaks, risk factors, and utilization of medical resources of respiratory syncytial virus-associated hospitalization (RSVH) in preterm infants in Taiwan. STUDY DESIGN:A Taiwan nationwide birth cohort was extracted from the Birth Certificate Application Database during 2007-2009 and prospectively linked to the National Health Insurance database. We evaluated the seasonal peaks and risk factors (gestational age [GA], chronologic age [CA], and bronchopulmonary dysplasia [BPD]) associated with the RSVH of preterm infants. The length of hospital stays (LOS), care in intensive care unit (ICU), and use of mechanical ventilation (MV) were also analyzed. RESULTS:There is a total duration of 9 months of RSVH season in Taiwan, three seasonal peaks and two seasonal peaks of RSVH in preterm infants with BPD and without BPD, respectively. Preterm infants had significantly higher RSVH rate than term infants (2.6% vs 0.9%, p<0.0001). Preterm infants born at 29-35 weeks of gestational age (wGA) with BPD had significantly higher RSVH rate than those without BPD (p<0.0001). Preterm infants without BPD born at < 32 wGA had higher RSVH rate than those born at 33-35 wGA (p<0.0001). Overall, 56.4% of RSVH occurred within 9 months of CA. Preterm infants with BPD had significantly higher ICU admission rate within 18 months of CA (p<0.0001), MV usage within 12 months of CA (p<0.0001) and LOS within 18 months of CA (p<0.001) than those without BPD. RSVH occurred within 6 months of CA was significantly associated with higher ICU admission rate (p<0.0001), MV usage (p = 0.0002) and longer LOS (p<0.001) in preterm infants without BPD. CONCLUSIONS:There is a total duration of 9 months of RSVH season in Taiwan. Preterm < 32 wGA, BPD, and CA within 6 months were risk factors of RSVH which also contribute to higher utilization of medical resources.